Diagnostic and Therapeutic Application of Ayurvedic Therapies in Raktapradar after Rajonivritti: A Case Study (International Journal of Ayurveda and Pharma Research, 2021)
Post-menopausal bleeding is reported in about 4 to 11percent of women. Its causes incudes several factors which may be benign or malignant. Benign factors can be managed at out-patient level and Ayurvedic procedures of Prakshalana and Pichu can be its alternative for management. Present case study is of post-menopausal bleeding where by the use of these Ayurvedic procedures, first the cause of bleeding was revealed and then, after removal of factor, it provided compete relief from bleeding. Thus, Ayurvedic procedures of Prakshalana and Pichu had two benefits in this case- diagnostic as well as therapeutic.